1994
DOI: 10.1111/j.1600-0714.1994.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

An unusual variant of keratoameloblastoma

Abstract: An unusual case of ameloblastoma which depicts cystic follicles containing orthokeratin, parakeratin, desquamated epithelium and necrotic material with dystrophic calcification is presented. The presence of ameloblast-like cells confirms the diagnosis of an ameloblastoma. However, certain features resembled those of the keratoameloblastoma and others, less convincively, the papilliferous keratoameloblastoma. The extensive keratinisation in this tumour and in the aforementioned neoplasms raises the question whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…The other term keratinizing ameloblastoma appears to have been an unfortunate choice, since this designation has been traditionally used for calcifying odontogenic cyst as described in the latter section. KA is exceptionally rare (8,12), and only 9 cases have been identified (11,(13)(14)(15)(16)(17). We consider the maxillary tumor of Lurie et al (18) to represent squamous odontogenic tumor rather than KA.…”
Section: Hybrid Tumor Of Ameloblastoma and Odontogenic Keratocyst (Kementioning
confidence: 99%
See 1 more Smart Citation
“…The other term keratinizing ameloblastoma appears to have been an unfortunate choice, since this designation has been traditionally used for calcifying odontogenic cyst as described in the latter section. KA is exceptionally rare (8,12), and only 9 cases have been identified (11,(13)(14)(15)(16)(17). We consider the maxillary tumor of Lurie et al (18) to represent squamous odontogenic tumor rather than KA.…”
Section: Hybrid Tumor Of Ameloblastoma and Odontogenic Keratocyst (Kementioning
confidence: 99%
“…Norval et al (13) suggested that KA should be considered as a variant of acanthomatous ameloblastoma. However, the following findings argue against this possibility.…”
Section: Hybrid Tumor Of Ameloblastoma and Odontogenic Keratocyst (Kementioning
confidence: 99%
“…It is well known that degenerative or necrotic tissues with or without dystrophic calcification may undergo actual conversion to bone, the process being termed pathologic ossification. [7] 35 Female Malay Right maxilla Massive, slowly-progressing swelling for 9 months 4 [7] 39 Female Chinese Anterior mandible Cystic lesion 5 [3] 26 Female Unknown Right mandible Firm swelling with pain for 5 years 6 [6] 26 Male AfricanRight maxilla Mass protruding from a tooth-extraction wound American…”
Section: Discussionmentioning
confidence: 99%
“…Of these, KA and PKA are extremely rare tumors, and our review of the English language literature yields only six cases of KA [3,6,7] and two cases of PKA [1,5]. The purpose of this paper is to report a keratoameloblastoma, which has an undescribed histological architecture within the spectrum of ameloblastoma.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation